Implementation of Argumentative Driven Inquiry in Science Learning 2009-2023: Bibliometric and Review Analysis - Misbah, Misbah; Hamidah, Ida; Sriyati, Siti; Samsudin, Achmad (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
This research examines research trends in applying argumentation-driven inquiry (ADI) in science learning and its potential for future research. A literature review is used in this research method through bibliometric analysis. The data source was obtained from the Scopus database, which obtained 72 articles from 549 articles in 2009-2023 with the keyword